Hypervalent Iodine Mediated Oxidative Cyclization of o-Hydroxystilbenes into Benzo- and Naphthofurans - Singh, Fateh V.; Wirth, Thomas (Synthesis, 2012)
A new and convenient metal-free cyclization of ortho-hydroxystilbenes into 2-arylbenzofurans and 2-arylnaphthofurans mediated by hypervalent iodine reagents is described. The cyclization products are isolated in good to excellent yields using stoichiometric (diacetoxyiodo)benzene in acetonitrile.
Keywords: benzofurans; cyclization; hypervalent iodine reagents; naphthofurans; stilbenes